Posted by **Jeconiah** on Monday, April 1, 2013 at 11:09pm.

Show proof of deriving the Quadratic Formula from the Quadratic Equation ax^2 + bx + c = )

## Answer this Question

## Related Questions

- Maths - Show proof of deriving the Quadratic Formula from the Quadratic Equation...
- algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...
- Algebra - can show me how to do this with out just squaring 3x^(1/2) - x - 6 = 0...
- Math - Use the quadratic formula to solve each of the following quadratic ...
- algebra - which quadratic formula would be used to solve the following quadratic...
- math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...
- QUADRATIC EQUATION - r^2+8r=48 First bring the 48 to the other side of the ...
- algebra - 0. Tell your classmates about your pet to set up the scenario for ...
- Maths - Hey my question is How do we get the triangular numbers sequence ( ...
- math-calculus - solve equation |x^2-2x-6| using quadratic formula. i not get how...